Randomized time‐varying knapsack problems via binary beetle antennae search algorithm: Emphasis on applications in portfolio insurance - Medvedeva, Marina A.; Katsikis, Vasilios N.; Mourtas, Spyridon D.; Simos, Theodore E. (Mathematical methods in the applied sciences, 2021)
The knapsack problem is a problem in combinatorial optimization, and in many such problems, exhaustive search is not tractable. In this paper, we describe and analyze the randomized time‐varying knapsack problem (RTVKP) as a time‐varying integer linear programming (TV‐ILP) problem. In this way, we present the on‐line solution to the RTVKP combinatorial optimization problem and highlight the restrictions of static methods. In addition, the RTVKP is applied in the field of finance and converted into a portfolio insurance problem. Our methodology is confirmed by simulation tests in real‐world data sets, in order to explain being an excellent alternative to traditional approaches.